Multiple Linear Regression and Correlation Analysis Of Yield of Summer Maize Varieties in Shaanxi Province, China (Bangladesh Journal of Botany, 2023)
The main factors affecting the yield of mid-ripening maize varieties were clarified to provide reference for breeding and production of summer maize varieties in Guanzhong Plain, Shaanxi Province. According to the relevant agronomic trait data of 11 new maize varieties planted in the Guanzhong Plain summer maize regional trial introduced in Shaanxi Province in 2019, analysis of the main characters of the new maize varieties were carried out using the multiple linear regression method. It can provide reference for the selection of maize agronomic traits. The agronomic traits that were significantly related to yield of summer maize varieties in Shaanxi Province were 100-grain 1weight, number of grains in row, seed rate, empty stalk rate and ear length, etc. When selecting maize varieties, under the premise of ensuring proper 100-grain weight and ear length, one should pay attention to the selection of varieties with high seed rate and low empty stalk rate. In the breeding of high-yielding maize varieties, lodging resistance should be enhanced, the rate of empty stalks should be reduced, the rate of seed production should be increased, 100-grain weight and ear diameter should be appropriately increased, and ear height should be reduced.Bangladesh J. Bot. 51(4): 979-985, 2022 (December) Special